Studies of Ni/Kaolinite Catalysts for the Hydrogenation of Toluene - G.M.S. ElShafei; T. Zaki; Gh. Eshaq; M. Riad (Adsorption Science & Technology, 2006)
No mention appears to have been made in the literature to the use of kaolinite as a support for nickel catalysts in the hydrogenation of toluene. In this study, kaolinite-supported Ni catalysts (1–7 wt%) were prepared and characterized, and their activity in the catalytic hydrogenation of toluene at atmospheric pressure established. XRD, DSC, N 2 adsorption and TPR methods were used as characterization techniques. XRD revealed that interaction occurs between the Ni species and the support at low Ni content (up to 3 wt%) but decreases as the Ni loading increases. This results in an increase in the number of Ni active sites with increased Ni loading and is reflected in the catalytic activity towards toluene conversion into methylcyclohexane, which increased as the Ni content of the catalyst increased. Modification by post-impregnation with KNO 3 or Zn(NO 3 ) 2 (2–6 wt% K or Zn) affected the extent of interaction between the Ni species and the support. Thus, the catalytic activity increased in the presence of 2 wt% modifier (K or Zn). However, at higher levels of modification (4 and 6 wt%), the catalytic activity decreased relative to that for the unmodified sample containing the same Ni loading. This loss in catalytic activity increased as the modifier content increased. Furthermore, in the presence of K as a modifier, the decrease in toluene conversion was accompanied by a shift in the temperature of maximum conversion from 200°C for the unmodified sample to a value of 250°C. This was attributed to the covering of the Ni active sites by some incompletely decomposed KNO 3 .